2001
DOI: 10.1007/s11746-001-0219-x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic esterification of (−)‐menthol with fatty acids in solvent by a commercial lipase from Candida rugosa

Abstract: Esterification of (−)‐menthol with fatty acids in isooctane was successfully catalyzed using a commercial lipase, Lipase AY “Amano” 30 from Candida rugosa in original powder form. The esterification reactions were performed to elucidate the effects of temperature, enzyme load, molar ratio of (−)‐menthol/fatty acid, and fatty acid type, keeping the (−)‐menthol concentration at 200 mM. At the optimal conditions for (−)‐menthol esterification, determined at a (−)‐menthol/lauric acid molar ratio of 1∶1 and 35°C [1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Esterification reactions in isooctane were carried out in a glass reaction flask (25 mL) at the optimal conditions determined for native Lipase AY in our previous study in duplicate (9). Heating of the water bath and stirring of the reaction mixture were performed with a magnetic stirrer equipped with a heating unit (Framo-Geraetetechnik M22/1 5655; Franz Morat KG, Eisenbach, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Esterification reactions in isooctane were carried out in a glass reaction flask (25 mL) at the optimal conditions determined for native Lipase AY in our previous study in duplicate (9). Heating of the water bath and stirring of the reaction mixture were performed with a magnetic stirrer equipped with a heating unit (Framo-Geraetetechnik M22/1 5655; Franz Morat KG, Eisenbach, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…4, with increasing temperature, the amount of 9c, 11t-CLA isomer in the FFA fraction started to decrease at first and then a slight increase could be observed that might be due to not being the temperatures that are more suitable for enzyme activity. Babali et al [17] and Kamiya et al [18] reported that the optimal reaction temperature for C. rugosa was around 35°C while Wang et al [19] showed that reaction temperature higher than 50°C caused the enzyme to be degraded and decreased the esterification of CLA with ethanol. They reported that 50°C and pH of 6.5 were optimal reaction conditions for total esterification.…”
Section: Temperaturementioning
confidence: 99%
“…The use of lipases enables to prepare optically pure products because of enzyme specificity. Many research works have reported that the lipase-catalyzed synthesis reactions of varies ester such as esterification of fatty acids with sugars, phospholipids, Lmenthol and vitamin C, etc., were carried out in nonaqueous system [10][11][12][13]. However, there is little research on the esterification of CLA with L-carnitine (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%